The Role of Social Capital, Sex Communication, and Sex Refusal Self-Efficacy in Sexual Risk Behaviors and HIV Testing among a Diverse Sample of Youth - David Cordova; Kate Coleman-Minahan; Tattiana Romo; Evelinn A. Borrayo; Sheana Bull (MDPI AG, 2022)
Social capital, namely civic engagement, adult support, and community support, shapes behaviors in meaningful ways, yet the literature examining the relationship between social capital and sexual risk behaviors and HIV testing among youth remains limited. This study examined the influence of social capital on sexual risk behaviors (i.e., unprotected sex, multiple sex partners, and being drunk or high prior to sex) and HIV testing among youth. A total of 200 primarily ethnic minority youth (mean age of 17.4 years) in Denver, Colorado were included in the study. Structural equation modeling findings indicate that higher levels of social capital were associated with unprotected sex and less HIV testing. Additionally, the association between social capital and sex with multiple partners was mediated by sex refusal self-efficacy. Youth may benefit from social capital, but it may not have the same protective or health-promotive value for youth as for adults.